Web application design handbook best practices for web-based software - Fowler, Susan L., 1953-; Stanwick, Victor R., 1958- (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2004)
"Susan and Victor have written the 'Junior Woodchucks Guidebook' of Web applications: Everything you need to know is in there, including tons of best-practice examples, insights from years of experience, and assorted fascinating arcana. If you're writing a Web application, you'd be foolish not to have a copy."--Steve Krug, author of Don't Make Me Think! A Common Sense Approach to Web Usability "Web sites are so nineties. The cutting edge of Web-design has moved to Web applications. If you are, like many Web designers, struggling to create dynamic, highly-functional Web-based applications, you need this book. It describes how Web applications differ from Web sites, and provides excellent guidance for common Web-application design problems, such as navigation, data input, search, reports, forms, and interactive graphic output."--Jeff Johnson, Principal Usability Consultant, UI Wizards, Inc., and author of Web Bloopers and GUI Bloopers "User interface designers have been debating among themselves for years about how to design effective Web applications. There were no comprehensive references that covered the myriad topics that emerged in these debates until Fowler and Stanwick took on the challenge and wrote Web Application Design Handbook, the first comprehensive guide to building Web applications. This book tackles design problems faced by every Web development team with uncommon wisdom, clear prose, and detailed examples. Key topics include: modifying the browser interface to meet application security and efficiency requirements, searching, sorting, filtering, building efficient and usable data input mechanisms, generating reports, preventing errors, and using creative visualization techniques to optimize the display of large sets of data. This thorough work should be a primary reference for everyone designing Web applications."--Chauncey E. Wilson, Principal HCI Architect, WilDesign Consulting "Every so often you run into a book and say to yourself: 'It's so obvious that this book should be read by every developer, so why wasn't it written years ago?' This is one of those books." --Scott Ambler, author of The Object Primer: Agile Model Driven Development with UML 2 The standards for usability and interaction design for Web sites and software are well known. While not everyone uses those standards, or uses them correctly, there is a large body of knowledge, best practice, and proven results in those fields, and a good education system for teaching professionals "how to." For the newer field of Web application design, however, designers are forced to reuse the old rules on a new platform. This book provides a roadmap that will allow readers to put complete working applications on the Web, display the results of a process that is running elsewhere, and update a database on a remote server using an Internet rather than a network connection. Web Application Design Handbook describes the essential widgets and development tools that will the lead to the right design solutions for your Web application. Written by designers who have made significant contributions to Web-based application design, it delivers a thorough treatment of the subject for many different kinds of applications, and provides quick reference for designers looking for some fast design solutions and opportunities to enhance the Web application experience. This book adds flavor to the standard Web design genre by juxtaposing Web design with programming for the Web and covers design solutions and concepts, such as intelligent generalization, to help software teams successfully switch from one interface to another. * The first interaction design book that focuses exclusively on Web applications. * Full-color figures throughout the book. * Serves as a "cheat sheet" or "fake book" for designers: a handy reference for standards, rules of thumb, and tricks of the trade. * Applicable to new Web-based applications and for porting existing desktop applications to Web browsers.
What is a Web application? -- The browser framework -- Data input : forms -- Data Input : lists -- Data retrieval : search -- Data retrieval : filtering and browsing -- Data output : reports -- Data output : printed forms -- Interacting with output -- Designing graphs and charts -- Graph types based on use -- Designing diagrams -- Diagram types -- Designing geographic maps -- Interacting with geographic maps -- Types of maps.
Includes bibliographical references (p. 611-632) and index.
Keywords: Web site development; Web sites -- Design; Application software -- Development; Electronic books